2005
DOI: 10.1302/0301-620x.87b3.15247
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of late developmental displacement of the hip

Abstract: The outcome of displaced hips treated by Somerville and Scott's method was assessed after more than 25 years. A total of 147 patients (191 displaced hips) was reviewed which represented an overall follow-up of 65.6%. The median age at the index operation was two years. During the first five years, 25 (13%) hips showed signs of avascular change. The late development of valgus angulation of the neck, after ten years, was seen in 69 (36%) hips. Further operations were frequently necessary. Moderate to severe oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 16 publications
3
62
1
2
Order By: Relevance
“…No hip in the group without OA had a CE angle \16°or MP over 31%. Long-term studies of patients previously treated for latedetected DDH have confirmed that residual subluxation is an important risk factor for later OA [2,8]. Hartofilakidis et al [17] followed the natural history of patients with subluxation (42 hips) who had not received any previous treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No hip in the group without OA had a CE angle \16°or MP over 31%. Long-term studies of patients previously treated for latedetected DDH have confirmed that residual subluxation is an important risk factor for later OA [2,8]. Hartofilakidis et al [17] followed the natural history of patients with subluxation (42 hips) who had not received any previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although persistent acetabular dysplasia and subluxation are risk factors for the development of osteoarthritis (OA) later in life [4][5][6][7], there is no consensus with regard to the degree of dysplasia that is of clinical significance or how long a time it takes for OA to become clinically manifest. Another controversial question is to what degree residual dysplasia changes during long-term follow-up [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-nine studies [1, 4, 6-8, 11, 13, 14, 16, 18-20, 23, 27, 29, 30, 34, 38, 40, 41, 45, 53, 54, 56, 61, 64, 67, 69, 72, 74, 77, 79, 81, 83-85, 89, 94, 96] [54], older than 6 months [5], between 6 and 18 months old [95], younger than 18 months [43], and younger than 24 months [87]; an anterior approach for patients 12 months or older [57,69]; and no operative treatment at all before 9 months of age [7].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Others have reported this procedure is risky and is difficult to reliably accomplish in practice. In 2005, a report by Angliss et al [1] looked at the long-term followup of nearly 150 patients who previously received open reduction for DDH. This article tried to determine early indicators that would help predict postoperative outcomes.…”
Section: The Limbusmentioning
confidence: 99%